Integrasi Project-Based Learning dalam Pendidikan Agama Islam: Strategi, Tantangan, dan Efektivitas - Rachman, Lutfi; Nurhanifansyah, Nurhanifansyah (Adabuna : Jurnal Pemikiran dan Pendidikan, 2024)
Education the current era increasingly recognizes Project-Based Learning (PBL) as an innovative approach to enhance student engagement and the relevance of learning. This research aims to explore the integration of PBL in Islamic Religious Education, focusing on the strategies employed, challenges faced, and the effectiveness of this approach. The study uses a mixed methods approach, with a quasi-experimental design and case studies involving 50 students and 5 teachers from two secondary schools. The results indicate that the implementation of PBL enhances students' understanding of Islamic religious material by an average of 17.5 points on the post-test scores. Additionally, students reported improvements in their motivation to learn, active engagement, and collaboration skills. Despite these positive outcomes, the research also identifies challenges in implementation, such as teacher readiness, limitations in resources, and time management. This study provides practical insights into the integration of PBL in the curriculum of Islamic religious education and its benefits in creating a more meaningful learning experience, aiming to serve as a reference for teachers and policymakers.